2015
DOI: 10.1016/j.jspd.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lumbar Spinal Subtype on Lumbar Intervertebral Disc Degeneration in Young and Middle-Aged Adults

Abstract: In this study, LSS was not statistically significantly correlated with LDD, nor was a high pelvic incidence protective against LDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 46 publications
1
15
0
3
Order By: Relevance
“…Morphological predictors of altered disc load outcomes were sagittal balance parameters in the thoracic spine and anatomic angles in the lumbar spine [19]. As expected, the Roussouly classification for categorizing the spinal alignments is inclusive and indicative, which considered most of the pelvic and spinal parameters [14].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Morphological predictors of altered disc load outcomes were sagittal balance parameters in the thoracic spine and anatomic angles in the lumbar spine [19]. As expected, the Roussouly classification for categorizing the spinal alignments is inclusive and indicative, which considered most of the pelvic and spinal parameters [14].…”
Section: Discussionsupporting
confidence: 60%
“…Rafael et al [9], for example, found that Roussouly type II sagittal alignment is significantly associated with early disc degeneration at the L4-L5 level, compared with type IV. However, Torrie et al [14] proposed that lumbar sagittal subtypes were not statistically significantly correlated with LDD. Therefore, the relationship between spinal sagittal subtypes and LDD has not been clearly explained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excluding extrinsic triggers of intervertebral disc degeneration, including physical activity ( 21 , 22 ), the parameters of lumbar spine sagittal alignment, including LL and PI, were considered to be strong predictors and serve a predisposing role in the pathogenesis of LDD diseases ( 12 , 23 ). SS, PI and LL have been observed to be different from type I to IV ( 5 , 23 ), thus, it was possible that different LSS (I-IV) may influence level-specific degeneration via specific biomechanical stressors. The Roussouly type II subtype is a flat lordosis that is characterized by mild thoracic and lumbar curvatures, with an SS of <35˚.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar disc degeneration (LDD), as the pathogenic cause of discogenic pain, has previously been correlated with lower back pain ( 3 ). The proportion of LDD still remains high in the asymptomatic population ( 4 , 5 ). The development of LDD has previously been described as a progressive process from mild to severe.…”
Section: Introductionmentioning
confidence: 99%